Gerakan Sosial Baru: Simbol #R4bia - Munadhil Abdul Muqsith (ADALAH, 2022)
This paper is to explain how the fusion of social movements and new media produces new social movements. The author himself raised how the #R4bia movement in Egypt and around the world as a form of protest and solidarity with the leader of the Egyptian state President Morsi (2012-2013) was overthrown by Abdul Fattah as-Sisi in a military coup in June 2013. The #R4bia symbol became a trending topic on various social platforms. media. technology is not historically a value-free entity. When a technology product interacts with the user community, the technology product undergoes an adjustment process, in which society gives meaning based on various values. There is a reciprocal relationship and a dialectical dynamic in the process of social construction that is built.